THE ROLE AND SIGNIFICANCE OF THE SHORT-TERM RESULT AND PRAXEOLOGICAL ANALYSIS OF THE COMPANY’S OPERATIONAL ACTIVITY (ON THE EXAMPLE OF PRZEDSIĘBIORSTWO GOSPODARKI KOMUNALNEJ W ŚREMIE SPÓŁKA Z O. O.) - Вартецький, Анджей; Єрмач, Веслав Жозеф (Socio-economic relations in the digital society, 2020)
The essence of the research is the cognitive and decision-making values of the result analysis and praxeological operational activity of the enterprise in a short period of time. The aim of the research is to indicate the role and importance of the above-mentioned decision-making instruments in the context of the dynamics of economic activity and quick feedback from the market. The subject of the considerations presented in the article is to present the role and importance of a short-term analysis of the resulting operational and praxeological activity of an enterprise (on the example of Przedsiębiorstwo Gospodarki Komunalnej w Śremie Spółka z o. o.). The essence of the considerations is contained in the specific solutions presented in the article in the field of controlling and indications of possible corrective and remedial actions, etc., e.g. the financial situation of the examined enterprise. Based on the results of the research, it can be concluded that the short-term financial analysis plays an important role in assessing the functioning of this type of companies. It is also an important instrument for optimizing activities and processes within the package of instruments, including those in the field of management engineering.